Eosinophilic oesophagitis: relevance of mast cell infiltration. Issue 3 (22nd June 2018) - Strasser, Daniel S; Seger, Shanon; Bussmann, Christian; Pierlot, Gabin M; Groenen, Peter M A; Stalder, Anna K; Straumann, Alex
Abstract : Aims: Eosinophilic oesophagitis (EoE) is a chronic inflammatory disease characterised clinically by symptoms of oesophageal dysfunction and histopathologically by a prominent eosinophilic inflammation. Despite eosinophils having a histologically predominant position, their role in the immunopathogenesis of the disease is still questionable. Several other inflammatory cells are involved and may also play a critical role. The purpose of this study was to characterise the mast cell infiltration, and to correlate it with the clinical state of EoE. Methods and results: Using immunohistochemistry and quantitative morphometry, we investigated eosinophils and mast cells extensively in oesophageal biopsies from patients with active EoE and from patients with EoE in remission, and compared the findings with healthy individuals. In EoE, epithelium and lamina propria were similarly infiltrated with eosinophils. In contrast, mast cells infiltration was limited to the epithelium, displaying a localised immune response. Interestingly, whereas epithelial mast cells and eosinophils were high in active EoE, some patients in remission, e.g. normalised epithelial eosinophils, showed remaining high numbers of mast cells. Patient clustering supported two groups of patients in clinical remission, differentiating based on presence or absence of epithelial mast cells. Conclusions: Active EoE is characterised in addition to the well‐known tissue eosinophilia by a marked epithelium‐restricted mast cell infiltration. Of interest, in a subgroup of patients, mast cell infiltration persisted despite clinical remission. To elucidate the clinical consequence of persistent epithelial mast cells infiltration further studies are required following patients in clinical remission longitudinally.